The effect of management change, audit opinion, and financial distress on auditor switching - Endistria Verosa Augustyvena; Romanus Wilopo (The Indonesian Accounting Review, 2017)
To avoid undesirable things related to auditor independence, some companies take an action to make mandatory auditor switching, but on the other hand, many other compa-nies make voluntary auditor switching. This study, therefore, aims to find out empirical evidence related to the factors, such as management changes, audit opinion, and financial distress, which affect the manufacturing companies to do voluntary auditor switching. The data used in this research are consumer goods industry sector companies listed on the Indonesia Stock Exchange during 2011-2015. A total of 33 manufacturing compa-nies are used as the sample. Analysis method used is logistic regression analysis. Overall, the finding shows that there is no significant evidence that management change, audit opinion, and financial distress have an effect on auditor switching. Suggestion for the future research is to extend survey area coverage and to add more variables that can influence auditor switching.